Food Security Status of Tribal People at Mohadevpur Upazila in Naogaon District - Sikder, MMH; Baten, MA; Ali, MA; Das, PK (Journal of Environmental Science and Natural Resources, 2017)
The study examines the food security analysis of households of tribal people at three villages of Mohadevpur Upazila of Naogoan District. Data were collected from a random sample of 63 where the total tribal people were 252. A structured interview schedule and focus group discussion were used for collecting data during July to September 2016. Food security condition of households of tribal people was measured on the basis of their per capita calorie consumption per day. Pearson’s Product Moment Coefficient Correlation (r) was computed to explore relationship of the respondents’ selected characteristics and their food security condition. The major findings of the study were that education level, house land size, cultivable area, annual household income, training experience, credit received and perceived strategies to increase food security had significant positive impact on food security (calorie intake) but age had significant negative impact on their household food security (calorie intake). Most of the households were (71percent) moderately food secured, 21 percent household had food secured and 8 percent households were low food secured per year. Government and NGOs should provide various types of training on agriculture and non-agriculture of tribal people. Government should take some safety net programs during climatic events such as drought, river erosion etc. Government, different NGOs and development agencies should give attention to improve their income through adopting some income generating activities. J. Environ. Sci. & Natural Resources, 10(1): 71-74 2017